PENGARUH THIN CAPITALIZATION, R&D EXPENDITURE, TRANSFER PRICING, TERHADAP TAX AVOIDANCE, PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Haitsamathif, Feubravally; Putri, Vidiyanna Rizal (Ibs Press, 2024)
This study aims to examine the effect of thin capitalization, r&d expenditure, transfer pricing on tax avoidance in mining companies listed on the Indonesian Stock Exchange (IDX). In this study, using control variables, namely profitability and firm size (Size). The sample in this study are mining companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. This study uses a sampling method in the form of purposive sampling using secondary data from financial statements and there are 22 banking companies listed on the Indonesia Stock Exchange (IDX) used in this study.